Caracterização química do óleo floral do muricizeiro (Byrsonima sericea) utilizado na reprodução por abelhas coletoras de óleo - Rosa, Felipe de Lima (2019)
The recent decline in population of generalist bees such as those of the genera Apis and Bombus has shown the need to breed and manage a larger number of bee species. Among the species with potential use for agricultural pollination in the Neotropics, a peculiar small group has specialised in collecting floral oil. Therefore, the aim of this study was to analyse the chemical profile and to identify the main constituents of the floral oil of the nance (Byrsonima sericea), an abundant species in the Northeast of Brazil and widely used by oil-collecting bees. A sample of 400 flowers of the nance were collected between October 2017 and January 2018. The samples were derivatised (MSTFA) and analysed by gas chromatography-mass spectrometry in a Model 7890B GC Gas Chromatograph System coupled to a Model 5977A MSD mass spectrometer. The compounds were separated using an HP-5ms capillary column and identified by comparing the mass spectra with the National Institute of Standards and Technology (NIST) database, and by comparison of the retention indices (RI). From the chromatographic analysis, it was possible to identify 23 constituents, especially fatty acids and carboxylic acids. The results indicate the presence of tricosanoic acid, palmitic acid and heneicosanoic acid as the main constituents of the oil under study. There is still a need for studies that would better explain the relationship of these constituents with the bees that use the oil.